Pancreatic Cancer - Neoptolemos, John P.; Urrutia, Raul; Abbruzzese, James; Büchler, Markus W. (Springer, 2016)
Epidemiology: world overview, risk factors, prospects for prevention -- Development and structure of pancreas -- Pathologic classification and biological behaviour of pancreatic neoplasia -- Developmental molecular biology of the pancreas -- Molecular pathology of precursor lesions of pancreatic cancer, pancreatic intraepithelial neoplasia (PanIN), intraductal papillary mucinous neoplasm (IPMN), and mucinous cystic neoplasm (MCN) -- Epigenetics: its fundamentals and applications to a revised comprehensive progression model for pancreatic cancer -- Molecular pathology of pancreatic neuroendocrine tumours MEN-1: gastrinomas, insulinoma, Non-Functioning Tumours, VIPoma, glucagonoma, Von Hippel-Lindau, Neurofibromatosis -- Sporadic neuroendocrine pancreatic tumours -- Molecular pathology of non-pancreatic cancer lesions: Ampullary cancer, intra-pancreatic bile duct cancer, and duodenal cancer -- Miscellaneous non-pancreatic non-endocrine tumours -- Novel molecular relationships between chronic pancreatitis and cancer -- Pancreatic cancer stem cells -- Cell cycle control: signalling pathways in pancreatic pathogenesis -- Apoptosis: signalling pathways in pancreatic pathogenesis -- EGFR: signalling pathways in pancreatic pathogenesis Pl3, Akt, lKK, Ras, Raf, MAPKK, ERK -- Hedgehog: signalling pathways in pancreatic pathogenesis -- Smad4/TGF-ß pathway: signalling pathways in pancreatic pathogenesis -- Notch signalling in pancreatic morphogenesis and pancreatic cancer -- Molecular characterization of pancreatic cell lines -- Mouse models of exocrine pancreatic cancer -- Principles and applications of microarray gene expression in pancreatic cancer -- Principles and applications of proteomics in pancreatic cancer -- Tumour-stromal interaction: invasion and metastases -- Genetic susceptibility, high risk groups, chronic and hereditary pancreatitis, familial pancreatic cancer syndromes -- Inherited endocrine pancreatic tumors associated with Multiple Endocrine Neoplasia Type 1 Von-Hippel-Lindau Syndrome, and Neurofibromatosis Type 1 -- Clinical decision making in pancreatic cancer -- Paraneoplastic syndromes -- Diagnostic and therapeutic response markers -- CT and fusion PET-CT Diagnosis, staging, and follow-up -- MRI and MRCP: diagnosis and staging of pancreatic cancer -- EUS Diagnosis and staging -- Laparoscopy and laparoscopic ultrasound: diagnosis and staging -- Overview of palliative management for pancreatic cancer -- Endoscopy -- Interventional radiology -- Role of palliative surgery in advanced pancreatic cancer -- Chemotherapy for advanced pancreatic cancer -- Developments in chemoradiation in advanced pancreatic cancer -- Surgical resection for pancreatic cancer -- Role of venous resection in pancreatic cancer surgery -- Pathological reporting and staging following resection -- Japanese Pancreas Society staging for pancreatic cancer -- Adjuvant chemotherapy in pancreatic cancer -- Case for adjuvant chemoradiation therapy for pancreatic cancer -- Case for neoadjuvant treatment in pancreatic cancer -- Borderline resectable disease -- Management of cystic neoplasms serous cystic neoplasms mucinous, cystic neoplasms, intraductal paillary mucinous neoplasms -- Laparoscopic surgery for pancreatic neoplasm -- Modern Japanese approach to pancreas cancer -- Development of novel biomarkers -- Inherited genetics of pancreatic cancer and secondary screening -- Gene therapy for pancreatic cancer -- Vaccine therapy and immunotherapy -- Emerging targets in pancreatic cancer.-